Acorenone B: AChE and BChE Inhibitor as a Major Compound of the Essential Oil Distilled from the Ecuadorian Species Niphogeton dissecta (Benth.) J.F. Macbr - James Calva (Pharmaceuticals, 2017)
This study investigated the chemical composition, physical proprieties, biological activity, and enantiomeric analysis of the essential oil from the aerial parts of Niphogeton dissecta (culantrillo del cerro) from Ecuador, obtained by steam distillation. The qualitative and quantitative analysis of the essential oil was realized by gas chromatographic and spectroscopic techniques (GC-MS and GC-FID). Acorenone B was identified by GC-MS and NMR experiments. The enantiomeric distribution of some constituents has been assessed by enantio-GC through the use of a chiral cyclodextrin-based capillary column. We identified 41 components that accounted for 96.46% of the total analyzed, the major components were acorenone B (41.01%) and (E)-β-ocimene (29.64%). The enantiomeric ratio of (+)/(−)-β-pinene was 86.9:13.1, while the one of (+)/(−)-sabinene was 80.9:19.1. The essential oil showed a weak inhibitory activity, expressed as Minimal Inhibitory Concentration (MIC), against Enterococcus faecalis (MIC 10 mg/mL) and Staphylococcus aureus (MIC 5 mg/mL). Furthermore, it inhibited butyrylcholinesterase with an IC50 value of 11.5 μg/mL. Pure acorenone B showed inhibitory activity against both acetylcholinesterase and butyrylcholinesterase, with IC50 values of 40.8 μg/mL and 10.9 μg/mL, respectively.